DESIGN AND STUDY OF DIMENSIONAL PARAMETERS INFLUENCE ON VORTEX TUBE BEHAVIOR - Branco, F. P.; Buchelt, E. D.; Barbosa, F. M.; Rosa, B. P.; Laporte, D. J. (Revista de Engenharia Térmica, 2019)
Vortex tube is a thermodynamic device, with no moving parts, applied to separate hot and cold air from compressed air injected into the tube. It has many applications in the industry, for example, among others, it can be mentioned electronic systems cooling, machining processes cooling and environmental chambers. This paper presents the design and tube dimensioning based on parameters and data found in the literature. Therefore, a prototype has been made and tested, which allowed the understanding of the influence of internal tube diameter and width on the hot and cold air temperatures while submitted to compressed air with pressure varying from 1 to 2.5bar. Results of tested configurations indicates that the relation between tube length and diameter (L/D) has small influence on vertex tube behavior, meanwhile, 3/8” tube diameter shows lowest temperatures on cold flow (-6.5°C, -8.0°C and -8.5°C) and higher COP (≈ 0.15).